An evaluation of the US African Growth and Opportunity Act (AGOA) trade arrangement with Sub-Saharan African countries - Moyo, Busani; Nchake, Mamello; Chiripanhura, Blessing (PSL Quarterly Review, 2019)
This paper evaluates the impact of the US African Growth and Opportunity Act (AGOA) trade arrangement on the growth of exports from Sub-Saharan African (SSA) countries. Using several variants of propensity score matching techniques, results show that the impact of AGOA on SSA exports is generally negative and statistically significant. The same conclusion is reached using the difference in differences (DID) method. Further, descriptive statistics show that the proportions of Africa’s exports going to the EU and the US since 2011 have been declining and the export shares of the three largest exporters to the US, namely, South Africa, Nigeria and Angola, are falling. JEL codes: F13, F14 Keywords: AGOA, SSA, propensity score matching